2.1.1 Model‐Based operational analysis for complex systems ‐ A case study for electric vehicles. Issue 1 (July 2014) - Doufene, Abdelkrim; Dauron, Alain; G., Hugo G. Chalé; Krob, Daniel
Abstract We present in this paper an operational analysis of a complex system following a Model Based Systems Engineering approach, illustrated by a case study on electric vehicles. We explain some strategic issues and reasons that make electric vehicles important and complex systems, and how these vehicles can significantly contribute to the European policies for sustainable development. We explain why it is necessary to apply a Systems Engineering approach to deal with the complexity of such systems, and we give an overview of the architectural design framework we follow. We present a model of the system of interest and of its environment built from the analysis of public documents and literature reviews. This allowed us to identify the key stakeholders, external interfaces, needs, use cases and operational scenarios. Based on this operational analysis, we present ways to pursue functional and trade‐off analyses.